USING FACEBOOK FOR ENGLISH LANGUAGE LEARNING: THE DIFFERENCES AMONG GENDER AND ETHNICITY - Kasuma, Shaidatul Akma Adi
This study investigates university students’ perceptions of using Facebook for English language learning (ELL) based on gender and ethnicities. A survey was used for data collection, in which all 622 participants reported to having at least one Facebook account which they frequently accessed multiple times a day. The findings show that the students possessed positive attitudes, motivation, and self-confidence in using Facebook to learn English language. They reported to have acquired new English words and sentence structures from their engagement with Facebook. In terms of gender and ethnicities, it is the female students, and the Indian respondents who illustrated highly positive perceptions of English language acquisition, motivation, attitudes, and self-confidence, when engaging with Facebook. The awareness of these differences and strengths between gender and among ethnicities, may assist the creation of more suitable learning strategies especially with the integration of Facebook and other social media.